2004
DOI: 10.1159/000080794
|View full text |Cite
|
Sign up to set email alerts
|

Female Age in ART: When to Stop?

Abstract: With increasing age the probability of ongoing pregnancy established by the use of assisted reproduction technology (ART) decreases. As a result the question arises whether age limits for the application of ART should be established. From a literature review and ongoing research data it appears that the costs per child born greatly increase after the age of 40 for both intrauterine insemination with mild ovarian stimulation and in vitro fertilisation treatment, while in cases of 44 and over, prognosis is flat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 143 publications
3
7
0
Order By: Relevance
“…We do not, however, consider this a drawback because all expenditures were inflated to correspond to 2005 prices, and we focused primarily on describing the differences in expenditures by women's age and socioeconomic position rather than the exact amount of euros. Furthermore, our cost estimation of a successful IVF cycle is in accordance with an earlier Finnish study [ 14 ] as well as earlier cost calculations by age that have included the same components as used in our study [ 10 ]. However, only some of the actual costs were taken into account, the costs excluded being non-routine radiological and laboratory tests and all indirect costs such as travel costs and sick leaves.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…We do not, however, consider this a drawback because all expenditures were inflated to correspond to 2005 prices, and we focused primarily on describing the differences in expenditures by women's age and socioeconomic position rather than the exact amount of euros. Furthermore, our cost estimation of a successful IVF cycle is in accordance with an earlier Finnish study [ 14 ] as well as earlier cost calculations by age that have included the same components as used in our study [ 10 ]. However, only some of the actual costs were taken into account, the costs excluded being non-routine radiological and laboratory tests and all indirect costs such as travel costs and sick leaves.…”
Section: Discussionsupporting
confidence: 70%
“…It is difficult to determine an optimal and equal age to stop the resource allocation for IVF. Treatment of selected women aged 40–43 has been found to be quite successful [ 10 , 19 ] and natural pregnancies also occur for women in their forties. However, a given age-limit could be a signal that encourages women to attempt to give birth during the normal fertile age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in fertility due to age cannot be compensated for by the current available ART and young women should be aware of this fact and plan their reproductive life accordingly (9). Candidates for COH-IUI should be carefully selected based on reliable predictors of success such as the levels of basal FSH and the antral follicle count (46). These women should be also advised of the increased risk of perinatal mortality and morbidity associated with a late pregnancy (47).…”
Section: Discussionmentioning
confidence: 99%
“…Tan et al (2014) reported a decrease of 13.2% in clinical pregnancy for women aged 40-44 years, compared to women less than 30 years. As concluded by Broekmans and Klinkert (2004), Lintsen et al (2007) and Templeton et al (1996), women age is considered the most important predictor of IVF success.…”
Section: Patient and Partner Variables As Pre-dictive Parametersmentioning
confidence: 96%